(untitled) (International Journal of Studies in Nursing, 2018)
Malnutrition is a major public-health problem throughout the developing world and is an underlying factor in over 50% of the 10-11 million children under 5 years of age who die each year of preventable causes. Uganda loses US310 million worth of productivity per year due to the high levels of stunting, iodine-deficiency disorders, iron deficiency, low birth weight, and malnutrition contributes to a loss of about 4.1% of the gross domestic product per year. This paper provides the findings of an assessment conducted in Kamuli district to determine the capacity of public health units to manage under-five malnutrition focusing on the six building blocks of the health system. This was a descriptive cross sectional study that employed both qualitative and quantitative methods of data collection, analysis and presentation. This involved interviewing health workers using a semi structured questionnaire and checklist for health facilities. Supplement qualitative data was collected using key informant interviews (KIIs). Results indicate that the capacity of health facilities to manage under-five malnutrition in Kamuli district was found to be low at 36.6% only. Capacity of health facilities was based on; Nutrition leadership and human resource development, health worker knowledge, availability of equipment and supplies, physical infrastructure, availability of infant and young child nutrition policy guidelines and planning and budgeting at health facility level.